KUALITAS PELAYANAN KARYAWAN FRONT OFFICE DI ANGKASA GARDEN HOTEL PEKANBARU - Noor Putri Ardianti; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Hotel is one type of accommodation that uses part or all of the part for lodging services, food and beverage providers and other services for the general public which are managed commercially. one of the departments in the hotel, one of which is the front office. Front office is the front office. in the context of the definition of a hotel, the front office is a department in the hotel which is located at the front. This study aims to determine the management efforts of the Angkasa Garden Hotel in maintaining the service quality of front office employees at the Angkasa Garden Hotel Pekanbaru. The method used in this research is quantitative with descriptive design. This study intends to collect data or descriptions related to employee services at Angkasa Garden Hotel Pekanbaru. Angkasa Garden Hotel Pekanbaru is a 3-star hotel founded by PT. Great Space Kencana. Angkasa Garden Hotel Pekanbaru was built on March 12, 2011, and began to be operational on June 10, 2012. The authors conclude that the service quality of Front Office employees at Angkasa Garden Hotel Pekanbaru is very good. This can be seen from the acquisition of each guest research that the author has described in the research questionnaire that the author has distributed to guests at Angkasa Garden Hotel Pekanbaru. With the results, namely the Reliability aspect with very good results, the Responsiveness aspect with very good results, the Assurance aspect with the Doubtful results, the Empathy aspect with very good results and the last Tangible aspect with very good results. From the results of the fifth aspect, the Assurance aspect has the lowest score among other aspects. Keywords : Service Quality, Front Office, Hotel